Кристалічна структура фаз серій Y1+x(Cu,Ga)4−x та Y3+x(Cu,Ga)11−x - Білявина, Н.М.; Марків, В.Я.; Тимошенко, М.В.; Тітов, Ю.О.; Слободяник, М.С. (Доповіді НАН України, 2011)
Методами монокристала та порошку визначено кристалічну структуру і уточнено склад шести багатих на галій фаз системи Y–Cu–Ga. Показано, що структури усіх цих фаз можна отримати з ромбічно деформованої підгратки типу BaAl4 кратним збільшенням її періодів (a й b) та частковим заміщенням пар атомів Cu/Ga на один атом Cu/Ga, який розташовується в базових сітках (Z = 0; 0,5): 1−Y1,02Cu1,35Ga2,63 (структура типу BaAl4, кратність 1×1), 2−Y1,04Cu1,12Ga2,84 та 3−Y1,0Cu1,0Ga3,0 (власний, 3×3), 4−Y1,08Cu0,57Ga3,35 (9×9), 5−Y3,025Cu4Ga6,975 та 6−Y3,23Cu3,07Ga7,70 (La3Al11, 3×1). By means of the X-ray single crystal and powder methods, the crystal structures and phase compositions of six Ga-rich phases of the Y–Cu–Ga system are investigated. It is shown that the crystal structures of all six phases can be obtained of the orthorhombic deformed sublattice of BaAl4-type structure by the multiple increase of its a and b lattice constants and by a partial replacement of pair copper/gallium atoms with one copper/gallium atom which is placed in the basic planes (Z = 0; 0.5): namely, 1−Y1.02Cu1.35Ga2.63 (BaAl4-type structure, 1×1 multiplicity), 2−Y1.04Cu1.12Ga2.84 and3−Y1.0Cu1.0Ga3.0 (own type structure, 3×3), 4−Y1.08Cu0.57Ga3.35 (9×9), 5−Y3.025Cu4Ga6.975 and 6−Y3.23Cu3.07Ga7.70 (La3Al11, 3×1).